2022
DOI: 10.5897/jece2021.0485
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the surface water around Odeama Community of the Niger Delta area of Nigeria

Abstract: Surface water quality in Niger Delta has been impaired over the years as a result of oil exploration and exploitation carried out in the region. This study investigates the anthropogenic influence on the water quality of Odeama creek. Water samples were collected during the wet and dry season from 20 sampling points and four control points and analyzed following standard methods and procedures. No statistical difference (p> 0.005) at 95% confidence interval was observed between sampling points except for nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The concentrations of TDS in water bodies are significantly influenced by the geological materials of the water [34]. The TDS reported in the crude oil-impacted water samples from Santa-Barbara River (mean value = 296.96 ± 5.02 mg/l) were found to be within the limits of ≤ 500 mg/l and ≤ 2000 mg/l recommended by the World Health Organization [15] and Federal Environmental Protection Agency of Nigeria [21], as well as below the limits of TDS (500 -48000 mg/l) often measured in brackish water [36]. The TDS values reported in water samples collected from hand-dug wells (mean value = 263.25 ± 4.13 mg/l) in communities surrounding the Santa Barbara River were also within the WHO and FEPA limits.…”
Section: Discussionmentioning
confidence: 62%
“…The concentrations of TDS in water bodies are significantly influenced by the geological materials of the water [34]. The TDS reported in the crude oil-impacted water samples from Santa-Barbara River (mean value = 296.96 ± 5.02 mg/l) were found to be within the limits of ≤ 500 mg/l and ≤ 2000 mg/l recommended by the World Health Organization [15] and Federal Environmental Protection Agency of Nigeria [21], as well as below the limits of TDS (500 -48000 mg/l) often measured in brackish water [36]. The TDS values reported in water samples collected from hand-dug wells (mean value = 263.25 ± 4.13 mg/l) in communities surrounding the Santa Barbara River were also within the WHO and FEPA limits.…”
Section: Discussionmentioning
confidence: 62%
“…Reports have also shown that, high nutrients content in aquatic ecosystem can reduce the level of oxygen available for aquatic organisms [8.9]. The oil activities in the Niger Delta Area of Nigeria have increased the levels of organic, inorganic and microbial contaminants in surface water bodies in the area [10,11]. Consequently, it has resulted in strange and common ailments among the inhabitants due to exposure to these toxic substances over time [12,13,14].…”
Section: Introductionmentioning
confidence: 99%